Prostate cancer imaging : an engineering and clinical perspective - El-Baz, Ayman S.; Pareek, Gyan; Suri, Jasjit S. (Boca Raton, FL : CRC Press, 2019)
This will be a comprehensive overview of the latest research, technologies and innovations in minimally invasive imaging of the prostate gland and prostate cancer imaging. A major focus will be 3D image segmentation along with computer-aided-diagnosis techniques for prostate cancer. Also featured are automated segmentation methods featuring ultrasound and MRI techniques. A number of the authors are world-class experts in the field ranging from the US, Europe, and Asia.
OCLC-licensed vendor bibliographic record.
Keywords: Prostate -- Cancer -- Imaging; Prostate -- Cancer -- Diagnosis; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / Urology; MEDICAL / Biotechnology